The The Portrayal of Male and Female Roles in English Language Textbooks Used in Vocational High School - Azizah, Nur; Setyono, Budi; Andayani, Made Adi (EFL Education Journal, 2022)
Gender is a crucial topic to explore especially in education context because it will affect the students’ understanding in a real life or around their society. It can not be denied if in textbook includes material which contains gender bias. Gender issues in the previous studies still depict gender stereotypes and biases, but some studies depict the positive images of gender. The present study examines through visual and verbal artifacts on ELT textbooks used in vocational high school and looks from gender roles. Using Fairclough’s (1995) model of Critical Discourse Analysis (CDA) as a method. The reveal showed that gender roles on the materials still depict gender biases however some gender discourse represent positive images. From this research suggests that the textbooks author must pay attention for developing materials in the textbooks.